Análise de padrões dos litígios ambientais no Tribunal de Justiça do Estado do Amazonas e a atuação do Ministério Público Estadual : uma aproximação à teoria da agência - Cavalcante, Bruno de Souza (2018)
The Public Ministry's Office has alternative dispute resolution mechanisms, with a view to administrative and extrajudicial ruling, some types of disputes, like the environmental crimes. To that end, once the unlawful conduct perpetrated against the environment has been identified, the Public Ministry's Office establishes a procedure to determine the fact, and, in the end, propose the mitigation of damage, through a transactional instrument called AEC - adjustment of environmental conduct. It occurs that, according to the evidences raised in the present study, the Public Ministry of the State of Amazonas has not limited itself to closing these cases with the subscription of the AEC, but, promoting in the judiciary the respective Criminal Action. This behavior suggests that the Public Ministry's Office is acting with redundancy in its works, with significant impact both for itself and for the Judiciary. Besides discouraging the criminal to sign the AEC, it increases the stock of actions in the Judiciary, and increases the transaction costs of Justice. The present work analyzes this phenomenon, approaching it of the Firm Theory, with emphasis in the relation of the Agent and the Principal. In the way of this fact, the World Bank report on the Brazilian judiciary in 2008 identified three sensitive points in services provided by Justice: delays, onerousness and unpredictability. The report in question provided the basis for the CNJ to enter into an agreement with the World Bank to modernize the Judiciary. Despite the initiative, the means of alternative dispute resolution provided for by law cannot be ignored and, to a large extent, they contribute to minimizing the number of lawsuits in process in Brazil, with consequences for procedural speed. In this sense, based on a statistical analysis, the present work focuses on the controversial Amazon State Public Prosecutor's – ASPP, demanding stance, in the treatment of illicit in environmental matters. Given that the Authority is not limited to resolving these conflicts at the administrative level, there is an increase in the number of actions, and consequent congestion in the cases of the Specialized Chamber on Environment and Agrarian Issues - SCEAI, of the Court of Justice of the State of Amazonas.